Molecular essence and endocrine responsiveness of estrogen receptor-negative, progesterone receptor-positive, and HER2-negative breast cancer. Issue 1 (December 2015) - Yu, Ke-Da; Jiang, Yi-Zhou; Hao, Shuang; Shao, Zhi-Ming
Abstract Background The clinical significance of progesterone receptor (PgR) expression in estrogen receptor-negative (ER–) breast cancer is controversial. Herein, we systemically investigate the clinicopathologic features, molecular essence, and endocrine responsiveness of ER−/PgR+/HER2− phenotype. Methods Four study cohorts were included. The first and second cohorts were from the Surveillance, Epidemiology, and End Results database (n = 67, 932) and Fudan University Shanghai Cancer Center (n = 2, 338), respectively, for clinicopathologic and survival analysis. The third and fourth cohorts were from two independent publicly available microarray datasets including 837 operable cases and 483 cases undergoing neoadjuvant chemotherapy, respectively, for clinicopathologic and gene-expression analysis. Characterized genes defining subgroups within the ER–/PgR+/HER2– phenotype were determined and further validated. Results Clinicopathologic features and survival outcomes of the ER–/PgR+ phenotype fell in between the ER+/PgR+ and ER−/PgR− phenotypes, but were more similar to ER−/PgR−. Among the ER−/PgR+ phenotype, 30 % (95 % confidence interval [CI] 17–42 %, pooled by a fixed-effects method) were luminal-like and 59 % (95 % CI 45–72 %, pooled by a fixed-effects method) were basal-like. We further refined the characterized genes for subtypes within the ER−/PgR+ phenotype and developed an immunohistochemistry-based method that could determine the molecular essence of ER−/PgR+ using three markers, TFF1, CK5, and EGFR. Either PAM50-defined or immunohistochemistry-defined basal-like ER−/PgR+ cases have a lower endocrine therapy sensitivity score compared with luminal-like ER−/PgR+ cases (P <0.0001 by Mann-Whitney test for each study set andP <0.0001 for pooled standardized mean difference in meta-analysis). Immunohistochemistry-defined basal-like ER−/PgR+ cases might not benefit from adjuvant endocrine therapy (log-rankP  = 0.61 for sufficient versus insufficient endocrine therapy). Conclusions The majority of ER−/PgR+/HER2– phenotype breast cancers are basal-like and associated with a lower endocrine therapy sensitivity score. Additional studies are needed to validate these findings.